Experiences in Reconciling Risk Management and Restorative Justice: How Circles of Support and Accountability Work Restoratively in the Risk Society. (March 2013) - Hannem, Stacey
Circles of Support and Accountability (COSA) is a restorative justice–based model that originated in Canada in the mid-1990s for the postincarceration reintegration of those who have offended sexually. Although the roots of COSA are in restorative justice philosophy, the program has also found favour, to some degree, with organisations such as police services and corrections that are traditionally concerned more with protecting community safety than with the ideals of restorative justice. Informed by the author's research and personal experience as a COSA volunteer, and analysis of recent and historical representations of COSA, this article explores theoretically how the development of the COSA initiative has been influenced by the seemingly disparate concerns of both the restorative justice and community protection movements, and examines the importance of balancing these paradigms in the everyday practices of circles.